Hepatocyte-Specific Co-Delivery of Zinc Ions and Plasmid DNA by Lactosylated Poly(1-vinylimidazole) for Suppression of Insulin Receptor Internalization - Akito Endo; Shoichiro Asayama (MDPI AG, 2021)
The lactosylated poly(1-vinylimidazole) (PVIm-Lac) with various lactosylated degrees has been synthesized for the co-delivery of zinc ions (Zn) and plasmid DNA (pDNA). The Zn/DNA/PVIm-Lac complex formation has achieved the specific delivery of zinc ions to HepG2 cells. Especially, the resulting hepatocyte-specific delivery of zinc ions has increased the number of insulin receptors on the cell surface. Consequently, the Zn/DNA/PVIm-Lac complexes have suppressed insulin receptor internalization on the surface of the HepG2 cells, expecting to offer unique therapy to inhibit hepatic insulin clearance.